2015
DOI: 10.3168/jds.2014-8330
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of purified β-casein variants A1, A2, B, and I: Effects on antioxidant and angiotensin-converting enzyme inhibitory capacity

Abstract: Genetic polymorphisms of bovine milk proteins affect the protein profile of the milk and, hence, certain technological properties, such as casein (CN) number and cheese yield. However, reports show that such polymorphisms may also affect the health-related properties of milk. Therefore, to gain insight into their digestion pattern and bioactive potential, β-CN was purified from bovine milk originating from cows homozygous for the variants A(1), A(2), B, and I by a combination of cold storage, ultracentrifugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 61 publications
2
43
1
2
Order By: Relevance
“…Whereas, Pleurotus eryngii possesses a pool of acid and basic proteases (Inácio et al , ) belonging to the families of aspartyl (Wang & Ng, ), serine (Cha et al , ) and metalloproteases (Shen et al , ), characterised by different active sites that hydrolyse the protein in several sites simultaneously, thus leading with a consequent increase in DH value. As shown in Table , DH values were significantly influenced by the CN haplotype ( P < 0.001), in agreement with Petrat‐Melin et al () who reported that the haplotype influences positively or negatively the presence of zones resistant to enzymatic hydrolysis. In fact, changes in the casein primary structure may alter enzyme cleavage sites, modifying both the structure of proteins and the behaviour of liberated peptides (Kamiński et al , ; Caroli et al , ).…”
Section: Resultssupporting
confidence: 89%
“…Whereas, Pleurotus eryngii possesses a pool of acid and basic proteases (Inácio et al , ) belonging to the families of aspartyl (Wang & Ng, ), serine (Cha et al , ) and metalloproteases (Shen et al , ), characterised by different active sites that hydrolyse the protein in several sites simultaneously, thus leading with a consequent increase in DH value. As shown in Table , DH values were significantly influenced by the CN haplotype ( P < 0.001), in agreement with Petrat‐Melin et al () who reported that the haplotype influences positively or negatively the presence of zones resistant to enzymatic hydrolysis. In fact, changes in the casein primary structure may alter enzyme cleavage sites, modifying both the structure of proteins and the behaviour of liberated peptides (Kamiński et al , ; Caroli et al , ).…”
Section: Resultssupporting
confidence: 89%
“…The method was performed according Petrat‐Melin et al . (). The factor of lysine residues in the collagen is 0.028, and the average molecular weight of amino acids in collagen is 99 g mol −1 .…”
Section: Methodsmentioning
confidence: 97%
“…The DH of collagen hydrolysates was quantified by N-terminal amines with fluorescamine (Udenfriend et al, 1972). The method was performed according Petrat-Melin et al (2015). The factor of lysine residues in the collagen is 0.028, and the average molecular weight of amino acids in collagen is 99 g mol À1 .…”
Section: Degree Of Hydrolysismentioning
confidence: 99%
“…Thus, the ability of food allergens to reach the jejunal mucosa is considered a prerequisite for allergenicity. While other studies have demonstrated the digestive stability of purified milk proteins, b-lactoglobulin and casein (Benedé et al, 2014;Peram, Loveday, Ye, & Singh, 2013;Petrat-Melin et al, 2015;Peyron, Mouécoucou, Frémont, Sanchez, & Gontard, 2006;Wal, 2001), few studies have examined the pepsin and/or pancreatin digestive stability of total bovine whole milk proteins. Moreover, limited digestibility studies have examined the immunoreactivity and potential allergenicity of digestive stable total bovine whole milk proteins, using allergen specific rabbit IgG antibodies and IgE antibodies from the sera of milk-allergic patients.…”
Section: Introductionmentioning
confidence: 98%